Criticism of Brazilian Academic Capitalism and the Commodification of Knowledge Raw Materials (London Journal of Research In Humanities and Social Sciences, 2025)
The present research seeks to analyze the logic of Brazilian academic capitalism that conditions a process of commodifying the production of knowledge, as well as prioritizing the offer of training courses for liberal professionals. This process is characterized as raw material knowledge contributing to the creation of a type of World Class University. Concerning the methodological procedures of the research, it was decided to develop a bibliographical and documental research based on the critical-dialectical epistemology. Content analysis was used in the treatment of data. Thus, the text is systematized in three parts: it analyzes the concept of crisis and how the capitalist economy was permeated by tensions throughout the year.
Keywords: inclusive education; theatre pedagogy; social cohesion; bullying prevention; reading theatre; Content; index; sign; Symbol; expression; duality; icon; attrition; Chetti Malay; Gen Y; Gen Z; language shift; loss; Higher education; Normalization; Student performance; Academic Writing; Generative AI; Cognitive offloading; Critical AI adoption; Naﶥ AI reliance; Learning patterns; Confirmation bias; Scaffolding elimination; Quasi-experimental study; Personalized learning; Metacognition; Academic integrity; Order; Brexit; crisis; Academic capitalism; Material Knowledge